265 THE NATURAL HISTORY OF FOOD ALLERGIES IN CHILDREN: AN EVALUATION OF CLINICAL TOLERANCE AND SEVERITY OF REACTIONS TO FOOD CHALLENGES. (1st January 2005) - Campbell, J. M.; Perry, T. T.; Christie, L.; Althage, K. A.; Carlisle, S. K.; Burks, A. W.; Parker, J. G.; Jones, S. M.
Abstract : Purpose: To compare food-specific IgE levels and age of passed or failed oral food challenges (FC) and examine the severity of failed FC. Methods: We performed a retrospective review of food allergic patients who underwent milk, egg, soy, wheat, and peanut FC (January 2000-June 2004) based on known predictive IgE levels. Food-specific IgE and age were determined for those who passed or failed challenges. System involvement and treatment of failed challenges were analyzed. Results: One hundred sixty-three FC were performed in 106 patients (67% male; 83% Caucasian; 66% atopic comorbidities). 56% of FC were blinded, 43% open. Negative challenges occurred in 97/163 (60%) - milk 47%, egg 61%, peanut 66%, soy 61%, and wheat 63%. Median age (years) of those passing challenges was: milk 3.2; egg 4.5; peanut 5.1; soy 2.3; wheat 3.6. For failed challenges median age was milk 2.0; egg 4.4; peanut 4.0; soy 4.6; and wheat 4.0. Median food-specific IgE levels (kUA/L) for passed FC were milk 1.6; egg 0.7; peanut 0.7; soy 0.7; and wheat 6.7. IgE levels for failed challenges were milk 4.5; egg 0.7; peanut 1.4; soy 20; and wheat 7.5. For failed challenges, 80% had cutaneous involvement, 32% upper respiratory, 23% lower respiratory, and 32% gastrointestinal. Positive challenges were successfully treated with antihistamines (80%), bronchodilators (8%), charcoal (2%), epinephrine (11%), and fluids/corticosteroids (2%), while 8% required no treatment. Conclusions: For patients with low food-specific IgE levels approaching 95th% negative predictive value, FC can be performed safely, with minimal symptoms and with the majority of patients showing clinical tolerance.